UPAYA PENINGKATAN PENGETAHUAN TENTANG STIMULASI DINI PERKEMBANGAN BALITA - Elsi Rahmadani; Susilo Wulan; Suryani Suryani; Novi Ade Suryani (COVIT (Community Service of Health), 2021)
Stimulation will develop faster than children who receive less or no stimulation. Children's development can be achieved optimally if parents, especially mothers, make various efforts to fulfill children's basic needs (care, sharpen, love) one of which is to stimulate children's development. The method of implementing this community service is by counseling about the knowledge of early stimulation of toddler development. This Community Service activity is carried out in the Work Area of ??the Bengkulu Fish Market Health Center. The time for implementation is in August 2021. The participants in this community service activity are mothers who have children aged 1-5 years in the Work Area of ??the Bengkulu Fish Market Health Center with a total of 35 people. Activities are carried out in stages (1) providing an explanation of the theme of the extension and the purpose of the activity; (2) do a knowledge pre test (3) provide knowledge about knowledge of early stimulation of toddler development (4) do a knowledge post test. The results of the activity showed that there was an increase in mothers' knowledge on average pretest 35.2 (poor category) and posttest ie 86.6 (good category). After participating in this activity, mothers can apply the knowledge of early stimulation of toddler development. Keywords: Child, Stimulation, Development